AN ANTHOLOGY OF GREEK EXPERIMENTAL ELECTRONIC MUSIC 1966-2016 - Koutsomichalis, Marinos (My University, 2019)
This anthology aspires to map the heterogenous landscape of Greek Experimental Electronic Music in all its contextual, sociopolitical, geographical and aesthetic disparity. With a single exception, it zeroes in on post-80s music. It comprises works of very different kinds by composers of all sorts of backgrounds that, still, can be thought of, as both 'Greeks' and 'Experimentalists'.
Keywords: electronic music